Muramyl Dipeptide Enhances Thermal Injury-Induced Autophagy and Inflammatory Cytokine Response of Lungs via Activation of NOD2/Rick Signaling Pathway in Rats. Issue 5 (November 2018) - Wu, Xiao-Jing; Liang, Hui; Zhang, Ying; Yang, Xu-Ming; Wang, Hong-Yu; Li, Hui; Li, Xin-Yi; Chen, Kai; Wang, Yan-Lin; Li, Jian-Guo; Zhang, Zong-Ze; Song, Xue-Min
ABSTRACT: Objective: Nucleotide-binding oligomerization domain 2 (NOD2) is the innate receptor of muramyl dipeptide (MDP). Our previous study revealed that MDP could enhance thermal injury-induced inflammatory cytokine production and organ function injury in rats. The present study was to determine the effect of MDP on autophagy and NOD2/receptor-interacting serine/threonine protein kinases (RICK) signaling pathway of lung injury after thermal injury. Methods: Forty male Sprague–Dawlay rats were randomly divided into four groups: normal control (NC) group, MDP group, Scald group, and MDP + Scald group. Scald group only suffered 20% total body surface area third-degree (TBSA) thermal injury. MDP group was only administered 5.0 mg/kg MDP through the left femoral vein; 5.0 mg/kg MDP was administered through the left femoral vein at 24 h after thermal injury in the MDP + Scald group. Results: TBSA thermal injury (20%) not only significantly increased the plasma inflammatory cytokines production, but also elevated the expression of LC3-I/II, the accumulation of autophagosome in the lung tissue. Compared with the Scald group, MDP + Scald double hit led to more serious inflammatory responses and higher expression of NOD2 mRNA, RICK, NF-κB p65, LC3-I/II, and the accumulation of more autophagosome in the lung tissue. Conclusions: MDP enhances thermal injury-induced autophagy and proinflammatory cytokine response of lung injury, which could be achieved via activating the NOD2/RICK signaling pathway in rats.